High prevalence of cutaneous warts in elementary school children and the ubiquitous presence of wart‐associated human papillomavirus on clinically normal skin. (1st January 2015) - de Koning, M.N.C.; Quint, K.D.; Bruggink, S.C.; Gussekloo, J.; Bouwes Bavinck, J.N.; Feltkamp, M.C.W.; Quint, W.G.V.; Eekhof, J.A.H.
Summary: Background: One‐third of Dutch primary school children have cutaneous warts; each year around 20% of them seek medical treatment. However, little is known about the epidemiology of the types of human papillomavirus (HPV) causing these warts. Objectives: To investigate the distribution of cutaneous wart‐associated HPV types in three primary school classes by analysing skin swabs taken from warts, and the forehead, hand dorsum and sole of the foot of included children. Methods: Using the hyperkeratotic skin lesion polymerase chain reaction/multiplex genotyping assay, each swab sample was used to genotype for 23 cutaneous wart‐associated HPV types. Results: Thirty‐one (44%) of the 71 children had a total of 69 warts, with a maximum of six warts per child. In the wart swabs, HPV2, HPV27 and HPV57, members of Alphapapillomavirus species 4, were most frequently detected (27%, 32% and 14%, respectively), whereas HPV1 was only found in two plantar warts. The prevalence of HPV carriage, detected in swabs of clinically normal skin of the forehead, left hand and left sole was 80%, with the most prevalent types being HPV1 (59%), HPV2 (42%), HPV63 (25%) and HPV27 (21%). Conclusions: Cutaneous wart‐associated HPV types were highly prevalent in primary school children, but did not correlate with the HPV types in warts. In contrast to the existing literature, HPV1 was frequently detected on clinically normal skin but was much less frequent in warts.